Pelaksanaan Pembebasan Bersyarat Bagi Narapidana Di Rumah Tahanan Negara (Rutan) Purwodadi Grobogan - Kurniawan, Putra Ari, Muchamad Iksan, S.H., MH, Marisa Kurnianingsih, S.H., M.Kn (2015)
Prisoners' rights in the form of prisoners guidance aren't always just be done at a penitentiary or jail but also at the outside of penitentiary or jail such as parole for the prisoners, according to article 1 letter b The Minister of Justice's adjudication Number M.01-PK.04.10 of 1999 on Assimilation, Parole and Furlough Before Exemption is a process of prisoners guidance outside the penitentiary which is held based on Article 15 and Article 16 Wetboek van Strafrecht voor Nederlandsch-Indie and also Article 14, 22, and 29 Act No. 12 of 1995 on Penitentiary. This study uses descriptive empirical juridical approach. Using the type of primary data and secondary data. Interviews and literature study are used as data collection techniques. By using qualitative data analysis. Based on the results of research and discussion that has been done, it can be summed that parole is granting exemption subject with some few conditions to the prisoners who have undergone the punishment for two-thirds of its sentence, this two-thirds is at least nine months. The parole execution of each submitted prisoners must meet the substantive and administrative requirements, furthermore the prisoners must obtain assurance from the family. In addition, prisoners are also given additional probation for a year and immediately added to the rest of the sentence.